Pollen morphology of subfamily Caryophylloideae (Caryophyllaceae) and its taxonomic significance. Issue 7 (26th March 2018) - Ullah, Fazal; Zafar, Muhammad; Ahmad, Mushtaq; Dilbar, Shazia; Shah, Syed Nasar; Sohail, Aamir; Zaman, Wajid; Iqbal, Majid; Bahadur, Siraj; Tariq, Akash
Abstract: The Pollen morphology of subfamily Caryophylloideae (Caryophyllaceae) from different phytogeographical region of Pakistan has been evaluated. In this research, 16 species belong to 6 genera of subfamily Caryophylloideae have been studied using light (LM) and scanning electron microscopy (SEM) for both qualitative and quantitative characters. Different palyno‐morphological features were observed including; pollen ornamentation, pore ornamentation, echini arrangement, echinidensity, number of pori, size of polar and equatorial diameter, P/E ratio, exine thickness, and size of pore were studied. The palyno‐morphological characters of subfamily Caryophylloideae have taxonomically significant in identification and delimitation of species. Two pollen types, i.e., subspheroidal (15 species) and prolate (one species Vaccaria hispanica ) were observed. Microechinate‐punctate and microechinate‐perforate pollen ornamentation were examined. Two pollen types of pori, i.e., prominent (5 species) and sunken (11 species) ornamentation have been reported. Three types of echini arrangement have been reported irregular, regular and rather regular, while three type of echinidensity (i.e., medium, dense and sparse) were observed. Pori numbers were found different in different species range from 5 in Silene apetala to 19‐35 in Silene vulgaris . Based on different palyno‐morphological characters, taxonomic key was develop for quick and accurate identification. The quantitative data were processed using SPSS software for average, minimum, maximum, and standard error. Abstract : SEM and LM were used for the palyno‐morphological characteristics of subfamily Caryophylloideae and its role in the identification of plant species. Identification and delimitations of species of subfamily Caryophylloideae base on micro‐morphological characters